Hubungan Pola Asuh Orang Tua Dengan Perkembangan Personal Sosial, Motorik Dan Bahasa Anak Prasekolah Di Paud Al-Hidayah - Yuswo Yani, Lasiyati (Jurnal Keperawatan Bina Sehat, 2012)
Child is unique individual and isn’t miniature of adult. So, they don’t treat like of adult. Beside that, child want especial care to optimal their development. Parenting style is one of factor that influence child development, if parenting style given, is not appropriate, so it will inhibit of child’s development. Objective research is knowing corelation of parenting method and social personal, motoric and languange development of pre school in PAUD AL-HIDAYAH Manyarsari-Gunungsari village, Dawarblandong district, Mojokerto regency. This design research used analytic method cross sectional approach. Technique of gathering sample used full method with 23 mother-child couples. Collecting data was done by questionnaire and KPSP and the result presented in forms cross tabulating. Result of research then there was corelation of parenting style and social personal, motoric and language development of pre school. It show that category of parenting is authoritative of 60,9%, permissive 21,7% and authoritarian 17,4%. Social personal, motoric, and language development is normal of 65,3%, doubted of 30,4%, and late of 4,3%. And the most parenting style is using authoritative parenting with normal development (52,3%) than parenting another. For that, the parent’s of children can understand some parenting then will give to their child so it will form good social personal, motoric and language development of children.Keywords: Parenting styles, Social personal, motoric, and languange development, child of pre school age